Level Of Anxiety Among College Students During COVID-19 Pandemic - Ranti Ekasari; Lilis Widiastuty; Dian Rezki Wijaya; Zilfadhillah Arranury; Tri Addya Karini; Ahmad Ahmad (Poltekkes Kemenkes Surakarta, 2022)
Background: The Coronavirus outbreak which has become a pandemic for more than a year could potentially cause health problems, including mental health. Mental health problems can occur to any group of people including the students because of the policy of learning from home using online learning technology. Mental health disorders or problems that may occur during the COVID-19 pandemic are high levels of anxiety. Methods: It was quantitative with a cross-sectional design study. The sample was 344 respondents that were collected through purposive sampling. It was available from 1 to 12 August 2021 using Depression Anxiety Stress Scales (DASS-42) Questionnaire via a google form. The data was analyze through frequency for univariate analysis and chi-square for bivariate analysis using statistical software Results: Based on the level of anxiety, the normal level was 13.1%; mild level was 8.7%; moderate level was 21.8%; severe level was 23.8%; extremely severe was 32.6%. The majority of respondents showed an extremely severe level of anxiety with a percentage. According to bivariate analysis, gender variable has a significant correlation to anxiety level while others have not. Conclusion: It is recommended for the college to provide and develop student counseling centers in order to support the psychological condition of students.